The knowledge level and practices on childhood injuries and interventions among parents at home - Devaraj, Navin Kumar (University of Malta, 2022)
Background: There are many common household emergencies that may involve children. These includes poisoning, falls, burns, choking, animal bites, febrile illnesses and febrile fits. Knowledge about preventive measures to avert these accidents at home as well as being familiar with first aid measures may help in preventing further complications and may aid in recovery. Therefore, this study aims to find out the general public knowledge regarding the preventive steps and early emergency steps that can be taken upon emergencies occurring among children. Methods: A cross sectional study incorporating a questionnaire/instrument that included brief socio-demographic data and 10 questions on common household injuries and emergencies, and either preventive steps or early interventions was used. Questionnaire was distributed among parents attending health talks at the Faculty of Medicine and Health Sciences, Universiti Putra Malaysia (UPM) between June 2019 to November 2019. The topics covered were on poisoning, falls, burns, choking, animal bites, high fever and febrile fits. Results: The total number of respondents was 119 parents. This study overall showed a good knowledge, attitude and practice among the parents towards common emergency inflicting children. Older aged and female parent were found to have more knowledge and positive attitude towards common emergencies among children, respectively. Conclusion: Group identified as having a lower knowledge, attitude and/or practice should be targeted in future community education programmes to increase the knowledge as well as to inculcate positive attitudes and practices towards identifying and managing common household emergencies among children.